Peningkatan Kompetensi Guru Sekolah Dasar Melalui Lesson Study (Sosialisasi LS bagi Guru SD N 1,2 Gentan Baki-Sukoharjo) - Slamet Hw, Slamet Hw; Subadi, Tjipto; Sutama, Sutama; Khotimah, Rita P. (WARTA, 2010)
Mathematics such as the assumption most people as a difficult lesson. This assumption is not entirely wrong because the average NEM value of elementary and middle school math is almost always located below the average value of the other lessons. The abstract nature of mathematics became the main obstacle to learning, especially for students who are still in the development of concrete or semi-concrete thinking. The situation is exacerbated by the use of methods which are still focused on the teacher (teacher center), not focused on students (child center) so that less activate students. Such conditions often found in schools both public and private. A reality that even when this has been attempted to improve the professionalism of teachers through workshops or upgrading, but the results can not be perceived by the public. Lesson study that is currently being developed in many universities believed to be able to increase the professionalism of teachers. Socialization and simulation results Leson Study conducted on January 13, 2010 against Elementary School teachers Gentan by the Development Team of Realistic Mathematic Education (RME) and Lesson Study- UMS concluded that: (1) The teachers were very enthusiastic and active during the socialization and stimulation, (2) The teachers want to know more about the RME and Lesson Study, (3) is hoping for a follow up such training so that teachers can implement lesson study in class, and (4) most teachers believe: by applying the approach RME through Lesson Study will help improve studentsâ understanding of math that the edges will help improve academic achievement.